Comment on “A single level tunneling model for molecular junctions: evaluating the simulation methods” by E. M. Opodi, X. Song, X. Yu and W. Hu, Phys. Chem. Chem. Phys., 2022, 24, 11958” - Bâldea, Ioan (Physical chemistry, chemical physics, 2024)
The present Comment demonstrates important flaws of the paper Opodi et al. Phys. Chem. Chem. Phys., 2022, 24, 11958 Their crown result (“applicability map”) aims at indicating parameter ranges wherein two approximate methods (called method 2 and 3) apply. My calculations reveal that the applicability map is a factual error. Deviations of I2 from the exact current I1 do not exceed 3% for model parameters where Opodi et al. claimed that method 2 is inapplicable. As for method 3, the parameter range of the applicability map is beyond its scope, as stated in papers cited by Opodi et al. themselves.
Gesehen am 24.05.2024